Primary Ewing's sarcoma/primitive neuroectodermal tumor of the ileum: case report of a 16-year-old Chinese female and literature review - Teng Li; Fang Zhang; Yarui Cao; Shoubin Ning; Yongmin Bi; Weicheng Xue; Li Ren (BMC, 2017)
Abstract Background Ewing's sarcoma (ES) and primitive neuroectodermal tumors (PNET) are closely related tumors. Although soft tissue ES/PNET are common in clinical practice, they are rare in the small intestine. Because of the absence of characteristic clinical symptoms, they are easily misdiagnosed as other benign or malignant diseases. Case presentation Here, we present the case of a 16-year-old female who complained of anemia and interval hematochezia. Her serum test results showed only a slight elevation of CA-125 and a low level of hemoglobin. Computer tomography and magnetic resonance imaging revealed a cystic and solid mass in the lower abdominal quadrant and pelvic region, which prompted suspicion of a malignant gastrointestinal stromal tumor of the small intestine. After resection, the tumor's histology and immunohistochemistry (positive for CD99, vimentin and synaptophysin) results suggested ES/PNET. Fluorescent in situ hybridization tests proved the breakpoint rearrangement of the EWSR1 gene in chr 22.Ultrastructural analysis revealed neurosecretory and glycogen granules in the tumor cell cytoplasm. Conclusions Together, these data supported the diagnosis of a rare case of localized ES/PNET in the small intestine without adjuvant chemo- or radiotherapy. To our knowledge, this is the first report from China of a primary small bowel ES/PNET in the English-language literature. In addition, on the basis of findings from previous publications and the current case, the optimal treatment for localized gastrointestinal ES/PNET is discussed.